PENGARUH RETURN ON EQUITY DAN TOTAL ASSETS TURNOVER TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Mia Agustin; Nugroho, Riski Dwi (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to determine the effect of Return On Equity and Total Asset Turnover on financial distress using the Altman Z-Score bankruptcy prediction approach. The research method used is a descriptive associative method with a quantitative approach. The population in this study were 83 food and beverage companies listed on the Indonesia Stock Exchange in 2019–2023. The sample in this study was determined using a purposive sampling technique and obtained 8 food and beverage companies with a five-year observation period so that the data obtained were 40 sample data. Hypothesis testing was carried out using panel data regression analysis with the help of the EViews 12 program and the significance level used was 5%. The results of this study indicate that simultaneously Return On Equity and Total Asset Turnover have a significant effect on financial distress with a significance value of 0.000000 <0.05 and an f-count of 24.09815> f-table (3.24). The determination coefficient obtained using Adjusted R-Squared is 0.542234 or 54.22%, while the remaining 45.78% is influenced by other variables outside this research model. Partially, Return On Equity has a positive and significant effect on financial distress with a significance of 0.0000 <0.05 and a t-count value of 6.018630> t-table (2.02107), while Total Asset Turnover does not have a significant effect on financial distress with a significance value of 0.0825> 0.05 and a t-count of −1.781015 <t-table 2.02107.